Investigating Turkish Pre-service Science Teachers’ Moral Reasoning in Genetics related Socioscientific Issues - Ümran Betül Cebesoy (Universitas Pendidikan Indonesia, 2020)
In this study, Turkish pre-service science teachers' moral reasoning patterns and the factors which influence their decisions while discussing genetics-related socio-scientific issues (SSI) were investigated. A basic qualitative approach was adopted for this purpose. Seven third-grade pre-service science teachers enrolled in the study. Semi-structured interviews for different genetics related SSI were conducted. The results revealed that decisions were generally based on the consequences of genetic applications (consequentialist) or based on moral principles or prescripts (principle-based). Most participants used consequence-based moral reasoning in their decisions, while principle-based moral reasoning was less used. They also used emotion-based moral reasoning. Their decisions were influenced by emotions, including empathy or sympathy toward the characters, or the unborn baby, in the scenarios. Additional and varied factors, including legal, ethical, economic, and technological concerns, were revealed as influential. Participants' decisions were also shaped by their own experiences, media resources, and faith in science. The implications for science teacher education programs are discussed.